The Schachter-Shalomi Collection Anchors Post-Holocaust American Judaism Archive at University of Colorado - Yuhas, Stephanie (Judaica Librarianship, 2016)
Rabbi Zalman Schachter-Shalomi, founder of Jewish Renewal, was a visionary teacher and leader who developed tools for transformation and helped a generation of Jewish Americans rekindle their faith. This article describes the acquisition, assessment, digitization and public access dimensions of the Schachter-Shalomi Collection housed at the University of Colorado, Boulder archives.